2016
DOI: 10.1038/sc.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of tuberculosis of spine and factors affecting neurological improvement in patients suffering from tuberculosis of spine: a retrospective analysis of 312 cases

Abstract: In management of patients suffering from tuberculosis of spine, levels of vertebral involvement, AIS grade at presentation, bladder and bowel involvement and its duration significantly affect the final neurological improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
1
24
1
2
Order By: Relevance
“…In our analysis of 783 bacteriologically/histopathologically confirmed cases of spinal tuberculosis, 677 (86.5%) patients had a typical MRI picture, which was comparable with the study conducted by A Sharma in New Delhi who found 264 (84.62%) patients had a typical MRI picture [ 30 ]. Conservative medical treatment in patients without deformities and neurological dysfunction resulted in clinically successful therapeutic responses in 93.8% of the patients in our study, which is close to Kotil K's research [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our analysis of 783 bacteriologically/histopathologically confirmed cases of spinal tuberculosis, 677 (86.5%) patients had a typical MRI picture, which was comparable with the study conducted by A Sharma in New Delhi who found 264 (84.62%) patients had a typical MRI picture [ 30 ]. Conservative medical treatment in patients without deformities and neurological dysfunction resulted in clinically successful therapeutic responses in 93.8% of the patients in our study, which is close to Kotil K's research [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the report by Peto et al [16], 50% of lesions were involved in the thoracic and lumbar spine. MRI and CT are still the most useful modalities for detecting spinal lesions, especially MRI, which has good sensitivity and specificity [17], shows lesions typical of discitis, detects epidural spread, and paraspinal abscesses earlier than other imaging studies [18].…”
Section: Discussionmentioning
confidence: 99%
“…These indications are the same as previously reported by Liang et al (18) as follows: (1) Both endplates of the diseased vertebrae shall be intact to provide a secure host bed for graft fusion. (2) kyphosis deformity should be < 60 0 . 3 Some potential shortcomings of this study should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal TB has increased because of the increased human immunodeficiency virus (HIV) epidemic and drug resistance. Lumbar tuberculosis is very threatening because it may lead to bone destruction, deformity, and paraplegia (1,2).…”
Section: Introductionmentioning
confidence: 99%